Strategies for Hydrogen-Enriched Methane Flameless Combustion in a Quasi-Industrial Furnace - Amaduzzi, Ruggero; Ferrarotti, Marco; Parente, Alessandro (Frontiers in Energy Research, 2021)
In this present work, simulations on a quasi-industrial 20kW Flameless Combustion chamber were carried out for hydrogen-enriched methane mixtures, to identify optimal geometrical configurations and operating conditions to operate in flameless combustion regime. The distinguishing feature of flameless combustion is the very strong interactions between chemical kinetics and fluid mixing, so that models based on the scale separation between turbulence and chemistry fail in predicting the main features of such combustion regime. The objective of this work is to show the advantages of MILD combustion for hydrogen-enriched fuels and the limits of current typical industrial designs for these mixtures. The performances of a semi-industrial combustion chamber equipped with a self-recuperative flameless burner are evaluated with increasing H$_2$ concentrations. For highly H$_2$-enriched mixtures, typical burners employed for methane appear to be inadequate to reach flameless conditions. In particular, for a typical coaxial injector configuration, an equimolar mixture of hydrogen and methane represents the limit for hydrogen enrichment. To achieve flameless conditions, different injector geometries and configuration were tested. Fuel dilution with CO$_2$ and H$_2$O was also investigated. Dilution slows the mixing process, consequently helping the transition to flameless conditions. CO$_2$, and H$_2$O are typical products of hydrogen generation processes, therefore their use in fuel dilution is convenient for industrial applications. Dilution thus allows the use of greater hydrogen percentages in the mixture.